Burden of mothers of children diagnosed with autism spectrum disorder: mixed method study - Jakelinne Reis Sousa Vilanova; Cristianne Teixeira Carneiro; Karla Nayalle de Souza Rocha; Mychelangela de Assis Brito; Ruth Cardoso Rocha; Adelianna de Castro Costa; Maria Augusta Rocha Bezerra (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective: To analyze the maternal burden related to the care of children diagnosed with autism spectrum disorder. Method: Study with a mixed-method sequential explanatory design held at the Association of Friends and Families of Special Children and in a WhatsApp® Messenger group, with 51 (quantitative phase) and six (qualitative phase) mothers, between January and October 2019. For data collection, in the quantitative phase, a sociodemographic, economic and child care characterization form and a Zarit Burden Interview instrument were used. Semi-structured interview was used in the qualitative phase. Descriptive bivariate and multivariate analysis (quantitative) and Bardin analysis (qualitative) were performed. Results: A total of 64.7% mothers felt burdened, with mild to moderate burden (52.9%). Four analytical categories on elements that trigger maternal burden emerged. Conclusions: There is an urgent need to identify maternal burden related to the care of children with autism spectrum disorder, during assistance in Primary Health Care.